A Detailed Review of Various Herbal Treatment Options for Potentially Curing or Ameliorating Pain in Diabetic Neuropathy - Wal, Pranay; Singh, Priya; Sinha, Aparna (Current Traditional Medicine, 2023)
Diabetes mellitus (DM) is a group of metabolic disorders associated with hyperglycemia due to deficient insulin secretion, insulin action, or both. In 2008, out of 36 million deaths due to non-communicable diseases, 1.3 million deaths alone were causative of DM, suggesting it to be a significant public health problem, reaching epidemic proportions globally. Diabetic Neuropathy is a common complication of DM. The pathophysiology of DN involves the interplay of metabolic and vascular factors, with the principal factor being hyperglycemia. Since DN is a prevalent, disabling condition associated with nerve injury, efficient treatments include glycaemic control and pain management. The ancient scriptures like Charak Samhita and modern pharmacology have corroborated the vast medicinal potential of herbal plants for achieving a more holistic treatment for several ailments. One of the primary objectives of the current review was to provide collective data on the available pharmacological evidence of selective herbal plants for future clinical translation. Also, the herbal extracts used in the studies need to be standardised according to standard protocols. This is important for understanding the complex effect of specific phytoconstituents at the biomolecular level and determining the clinical dose to make results more repeatable.
Keywords: ameliorating pain